Progress is not linear, it’s cyclical : old books and our field’s enduring vision – a modest proposal for readers of the SJRCC - James Anglin (Scottish Journal of Residential Child Care)
I love books. Perhaps you do too. My passion for books really took hold when I discovered the book stacks in the library of my university during my first undergraduate semester. I fell in love with walking the rows and rows of books, on all subjects and disciplines. I loved the musty smell, and the phantasmagoria of shapes, sizes and colours.